THE IDEA OF THE GOOD - De Koninck, Thomas (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2020)
In this inaugural address, we will concentrate on the status and role of the good. The good is said in many ways just as “being” is. It is neither univocal nor purely equivocal but analogous, with a primary meaning to which all other meanings ultimately refer, taken from substance. And speaking of God, he is seen as the ultimate cause of motion through books seven and eight of Aristotle’s Physics; as first intelligible in Lambda 7 and 9; and as the primary good in this chapter 10. Now the good in that sense is the ultimate telos – the end – of everything, drawing everything to itself.